MIKROENKAPSULASI KONSENTRAT ASAM LEMAK TAK JENUH DARI MINYAK IKAN PATIN - Siti Zakiyatul Khamidah; Ema Hastarini; Dedi Fardiaz; Slamet Budijanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Catfish fillet processing industries produce several wastes, such us belly flap. This part has high fat content that can be a source of essential fatty acids. This research aimed to evaluate the physicochemical characteristics of the unsaturated fatty acids obtained from pangasius fish encapsulated with maltodextrin and sodium caseinate at different combinations. To determine the best combination of maltodextrin and sodium caseinate with ratio 90/10, 80/20, and 70/30, parameters such as emulsion viscosity, product yield, microencapsulation efficiency, encapsulated oil yield, water solubility, morphology and whiteness were measured. Based on the results, maltodextrin and sodium caseinate ratio of 70/30 was the most optimal because it resulted in the highest values in terms of microencapsulation efficiency (63.08%) and oil micro-encapsulation yield (24.13%).